Induction of An Oral Sensitization Model in Rats - Camps-Bossacoma, Mariona; Abril-Gil, Mar; Franch, Angels; J. Perez-Cano, Francisco; Castell, Margarida (Clinical Immunology, Endocrine & Metabolic Drugs (Discontinued), 2014)
Animal models of food allergy can provide advances in the aetiology, pathogenesis and therapeutic treatment of this disease. The aim of the present study was to set up a model of oral sensitization in rats by testing seven different procedures and using ovalbumin (OVA) as the antigen. Brown Norway and Lewis rats aged between three and eight weeks old received, orally, different doses of the OVA together with or without cholera toxin (CT) under several dosages. Isotypes of anti-OVA antibodies were determined weekly in serum and also in intestinal samples (faecal or gut lavage). In the most successful procedure, mesenteric lymph nodes (MLN) and intestine samples were excised to determine cytokines and gene expression related to allergic response, respectively. In both Brown Norway and Lewis rats, the quantification of specific antibodies revealed that CT was required to increase oral sensitization. In addition, OVA dosage, age and sex of animals are important in the oral sensitization of Lewis rats. Serum anti-OVA antibodies mainly belonged to IgG1 and IgG2a isotypes, and intestinal anti-OVA immune response was almost undetectable. Specific IgE was not found in the serum of any of the studied procedures, and cytokines from MLN did not clearly demonstrate a Th2 immune response. The gene expression study in small intestine samples of sensitized rats suggested changes in IL-10 and TLR-5 mRNA expression. In summary, oral sensitization in rat could be achieved in both young Brown Norway and young female Lewis rats.
Keywords: cholera toxin